Energy conversion efficiency in the electromechanical system with magnetic gear of passenger electric transport rolling stock - Ostroverkhov, Mykola; Spinul, Liudmyla; Veshchykov, Heorhii (Technology audit and production reserves, 2025)
The object of research is electromechanical processes in the traction electric drive of the rolling stock of passenger electric transport under the action of strong and short-term moments of disturbance during acceleration, movement at a steady speed and deceleration. The problem under consideration was to determine the influence of the parameters of the magnetic reducer on reducing the effect of external disturbances on the electromechanical system of the rolling stock of the metro. The analysis was carried out on the basis of a comparison of a typical traction electric drive with a mechanical reducer and the proposed electric drive with a magnetic reducer. This reducer transmits the moving moment to the wheel pairs without mechanical contact, but at the same time causes an elastic-viscous connection between its input and output shafts. A comparison of the behavior of the electromechanical system using a typical mechanical reducer and the proposed magnetic reducer is presented. The influence on the efficiency of energy conversion of the parameters of the magnetic reducer, in particular the magnetic stiffness and the damping coefficient, is investigated. During the research, differences were found in the dependences of the amplitude of moments, the period of natural oscillations, and the time of damping of the transient process for two types of gearboxes. With a stiffness of the magnetic gearbox of 5000 Nm/rad, the amplitude of the moment decreased by 59% compared to the mechanical gearbox. The period of natural oscillations decreased by 62%, and the damping of the transient process increased by 59%. The research results showed that the rational choice of the parameters of the magnetic gearbox allows to increase the dynamic stability of the electric drive to short-term disturbances. At the same time, shock loads on the motor shaft and the amplitude of torque fluctuations are reduced. This is especially relevant for traction systems of transport operating in conditions of uneven resistance to movement. The practical value of the research results lies in the possibility of improving the efficiency of energy conversion and the quality indicators of control of the traction electric drive of the rolling stock of passenger electric transport. This research will be useful for scientists and companies specializing in the field of rolling stock of passenger electric transport.